2011
DOI: 10.1051/0004-6361/201015190
|View full text |Cite
|
Sign up to set email alerts
|

Spin period evolution of a recycled pulsar in an accreting binary

Abstract: We investigate the spin period evolutions of recycled pulsars in binary accreting systems. Taking both the accretion induced field decay and spin-up into consideration, we calculate their spin period evolutions influenced by the initial magnetic field strengths, initial spin periods, and accretion rates. The results indicate that the minimum spin period (or maximum spin frequency) of a millisecond pulsar (MSP) is independent of the initial conditions and accretion rate when the neutron star (NS) accretes the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 71 publications
2
25
0
Order By: Relevance
“…These bimodal distributions in magnetic fields and spin periods are shown, e.g., in Fig. 1 in Wang et al (2011) and also Fig. 1 of this paper, which, with data taken from ATNF pulsar catalogue, shows a large population of normal pulsars and a smaller population of MSPs.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…These bimodal distributions in magnetic fields and spin periods are shown, e.g., in Fig. 1 in Wang et al (2011) and also Fig. 1 of this paper, which, with data taken from ATNF pulsar catalogue, shows a large population of normal pulsars and a smaller population of MSPs.…”
Section: Introductionsupporting
confidence: 71%
“…We have tested the accretion-induced field-decay and spin-up model for recycled MSPs (Zhang & Kojima 2006;Wang et al 2011). In our computation, we have considered lognormal distributions of initial B and P in the range of B 0 = 10 10.5 −10 14 G and P 0 = 0.1−30 s, a Gaussian neutron star mass distribution in the range of M = 0.9−2.2 M , a uniform neutron-star radius distribution of R = 10−20 km, a lognormal distribution of the accretion rate ofṀ = 10 16 −10 18 g/s, and an accretion time of Δt = 10 7 −10 9 yr. We found that the computed B and P distributions of recycled MSPs are insensitive to mild variations in the width of the initial distributions.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…The spin period of a dead pulsar should satisfy P 2 s > B /1.7 × 10 11 (Bhattacharya et al 1992) and the upper limit of the spin period for normal radio pulsars is 11 s (Manchester 2004). Wang et al (2011) proposed that the minimum spin period of the NS is insensitive to its initial spin period and magnetic field. Therefore, we adopt an initial spin period of P s, i = 10 s and initial magnetic field of B = 10 12 G for the accreting NS.…”
Section: Resultsmentioning
confidence: 99%